Correction: Conversion of landfill gas to liquid fuels through a TriFTS (tri-reforming and Fischer–Tropsch synthesis) process: a feasibility study. Issue 8 (24th June 2019) - Zhao, Xianhui; Naqi, Ahmad; Walker, Devin M.; Roberge, Tim; Kastelic, Matthew; Joseph, Babu; Kuhn, John N.
Abstract : Correction for 'Conversion of landfill gas to liquid fuels through a TriFTS (tri-reforming and Fischer–Tropsch synthesis) process: a feasibility study' by Xianhui Zhao et al., Sustainable Energy Fuels, 2019, 3, 539–549.